The rise of blockchain technology in agriculture - Kamilaris, Andreas; Prenafeta-Boldú, Francesc Xavier; Fonts, Agusti (Technical Centre for Agricultural and Rural Cooperation, 2018)
Blockchain appeared in our lives as a modern technology that promises ubiquitous business transactions among distributed untrusted parties, without the need of intermediaries such as banks. Several ongoing projects and initiatives now illustrate the impact blockchain technology is having on agriculture and suggest it has great potential for the future.